Exploring the structural properties and enhancement of Opto-electrical investigations for the synthesized epoxy based polymers with local nanoscale structures - Wissal Jilani; Najla Fourati; Chouki Zerrouki; Pierre-Antoine Faugeras; Alain Guinault; Rachida Zerrouki; Hajer Guermazi (Materials Research Express, 2020)
Epoxy networks of the diglycidyl ether of bisphenol A (DGEBA) were prepared using 4, 4′-diaminodiphenyl (44′DDS) and 3, 3′-diaminodiphenyl (33′DDS) sulfone diamines crosslinking hardeners. The structural, linear optical and mechanical properties of the investigated sample were analysed. Dynamic Mechanical Thermal Analysis and wide-angle x-ray diffraction were conducted to select a candidate presenting interesting thermo-mechanical properties and particular nanostructures embedded in an amorphous matrix. Our choice is therefore focused on DGEBA/33′DDS polymer for which, rocking curve measurements revealed the existence of two principal reflecting planes inclined to each other by about 0.27°. To highlight the potential effect of these interfaces, Thermally Stimulated Depolarization Current (TSDC) and Time Domain Spectroscopy measurements have been carried out. The application of the windowing polarization TSDC technique, in DGEBA/33′DDS polymer sample, gives an almost linear variation of the activation energies in the range between 3.65 and 4.09 eV. To our knowledge, this is the first study concerning epoxy polymers in which activation energies associated to ρ interfacial charge relaxations are calculated. To study the effect of the interfaces and trapped charge carriers, correlated by the angle x-ray diffraction measurements, the optical parameters were investigated. Our contribution will open a new avenue for developing the DGEBA/33′DDS polymer sustainable candidate in optoelectronic engineering applications.